2020
DOI: 10.3390/ijms21186649
|View full text |Cite
|
Sign up to set email alerts
|

Flying Together: Drosophila as a Tool to Understand the Genetics of Human Alcoholism

Abstract: Alcohol use disorder (AUD) exacts an immense toll on individuals, families, and society. Genetic factors determine up to 60% of an individual’s risk of developing problematic alcohol habits. Effective AUD prevention and treatment requires knowledge of the genes that predispose people to alcoholism, play a role in alcohol responses, and/or contribute to the development of addiction. As a highly tractable and translatable genetic and behavioral model organism, Drosophila melanogaster has proven valuable to uncov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 228 publications
0
19
0
Order By: Relevance
“…Many of the genes implicated in mammalian alcohol reactions and human AUD have conserved functions in Drosophila (Grotewiel and Bettinger, 2015;Lathen et al, 2020). Some of these involve common molecular pathways for alcohol response, such as cyclic adenosine monophosphate (cAMP) (Moore et al, 1998) and neuropeptide Y (neuropeptide F in flies) (Wen et al, 2005).…”
Section: Mechanistic Validitymentioning
confidence: 99%
“…Many of the genes implicated in mammalian alcohol reactions and human AUD have conserved functions in Drosophila (Grotewiel and Bettinger, 2015;Lathen et al, 2020). Some of these involve common molecular pathways for alcohol response, such as cyclic adenosine monophosphate (cAMP) (Moore et al, 1998) and neuropeptide Y (neuropeptide F in flies) (Wen et al, 2005).…”
Section: Mechanistic Validitymentioning
confidence: 99%
“…Here, it is worth noting that NPY is of major interest to substance misuse disorders and has been implicated in human alcohol use disorder[ 137 - 139 ] as well as in rodent models[ 140 - 142 ]. Since genetic vulnerability remains the core disease-causing factor for humans, and given that unbiased genetic screening, QTL analyses or GWAS studies are easily paired with functional studies in D. melanogaster [ 143 , 144 ], the latter presents as a viable alternative organism to study gene-environment interactions and the triggers that drive alcoholism, with perhaps the next step being a pursuit of the epigenetic mechanisms underlying those pathologies.…”
Section: Epigenetic Modifications Identified By Transgenerational Studies Of D Melanogaster Relevant To Psychiatrymentioning
confidence: 99%
“…Additionally, Drosophila is a valuable model for studying complex addictive disorders such as alcoholism [ 26 ]. Studies over the last 25 years have shown that flies express a range of alcohol-induced behaviors similar to those observed in intoxicated humans [ 27 ], and numerous genes isolated based on their involvement in Drosophila alcohol responses have helped identify corresponding genes that contribute to alcohol use disorder (AUD) in humans [ 28 ]. Additionally, the neurotransmitters important for mammalian alcohol-induced behaviors are also involved in Drosophila alcohol responses [ 29 ], including dopamine, which is required for reward in flies [ 26 ] and in humans [ 30 ].…”
Section: Introductionmentioning
confidence: 99%